Conformation traits of dairy cattle populations in selected Districts of Northwestern Amhara, Ethiopia - MISGANAW MAMMO; KEFYALEW ALEMAYEHU; ASAMINEW TASSEW (Society for Indonesian Biodiversity, 2017)
Mammo M, Alemayehu K, Tassew A. 2017. Conformation traits of dairy cattle populations in selected Districts of Northwestern Amhara, Ethiopia. Biodiversitas 18: 1669-1679. The study was conducted in three selected districts of northwestern Amhara. The objective was to quantify the characteristics of conformation traits of dairy cattle populations at smallholder farmers' level. 279 cattle keepers were selected for measurement of conformation traits. About 105 indigenous cattle from each district and 42 crossbred female cattle were considered for measurement. SPSS (2007) was used to analyze qualitative data and SAS (2014) for quantitative data. The results revealed that the conformation trait measurements (cm) of indigenous cattle had significant variation (P< 0.001) on neck length for dairy type (54.07 ± 4.80) and meat type (51.96 ± 4.05) traits. The width at the point of the shoulder was 7.72 ±1.96, 6.60 ± 1.68 and 5.35 ± 1.61 for meat type, dual type and for dairy type cattle, respectively. A male cattle had significant variation over female except neck length. All qualitative traits were laid intermediate levels (4-6 point) except crossbred which was 63.64 %. About 30% of dairy type cattle had high rear udder depth and 43.33% dairy type cattle had strong central ligament. Crossbred cattle had 42.1% sickled rear leg. In general, about 57.5% dairy type cattle and 95.2% crossbred cattle have very angular shape as 75% of meat type cattle lack angularity. From this research, it could be concluded that there were significant differences of conformation traits between dairy type and beef type cattle from the cattle population considered in the study for developing specialized dairy or beef breed types. As well as indigenous dairy type cattle are comparable to other known dairy cattle breeds like Kanan, Fogera and Barka. However, farmers did not exercise in developing product specific and specialized breeds with their corresponding production system than multipurpose. Thus, selection and appropriate planed breeding program is crucial for future dairy cattle genetic improvement to match genotype and environment and meet producers’ production objectives. Hence, conformation traits can be a vital tool to make decisions on cattle selection and breed improvement.